2016
DOI: 10.1136/bmjopen-2015-009986
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal exposure to cannabis and maternal and child health outcomes: a systematic review and meta-analysis

Abstract: ObjectiveTo assess the effects of use of cannabis during pregnancy on maternal and fetal outcomes.Data sources7 electronic databases were searched from inception to 1 April 2014. Studies that investigated the effects of use of cannabis during pregnancy on maternal and fetal outcomes were included.Study selectionCase–control studies, cross-sectional and cohort studies were included.Data extraction and synthesisData synthesis was undertaken via systematic review and meta-analysis of available evidence. All revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
439
5
15

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 487 publications
(472 citation statements)
references
References 41 publications
13
439
5
15
Order By: Relevance
“…28 A recent systematic review and meta-analysis also noted an increase in NICU admission among neonates exposed to cannabis in utero (pooled OR 2.02, 95% CI 1.27–3.21). 6 The observed increased risk of NICU admission in these and other studies 29 , coupled with our finding of increased neonatal morbidity, emphasizes the need to rigorously evaluate neonatal morbidity in this population.…”
Section: Commentmentioning
confidence: 55%
“…28 A recent systematic review and meta-analysis also noted an increase in NICU admission among neonates exposed to cannabis in utero (pooled OR 2.02, 95% CI 1.27–3.21). 6 The observed increased risk of NICU admission in these and other studies 29 , coupled with our finding of increased neonatal morbidity, emphasizes the need to rigorously evaluate neonatal morbidity in this population.…”
Section: Commentmentioning
confidence: 55%
“…Cannabis use poses other significant health risks, which increase with the frequency and intensity of use: 1) central nervous system impairment, acute (e.g., judgment, coordination) and chronic (e.g., memory, cognition), 29 2) exacerbation and persistence of psychiatric symptoms (e.g., depression, psychosis), 30 3) development of other drug use disorders, including nicotine and alcohol 31 4) prescription medication interactions (e.g., antidepressants, opioids), 32 5) prenatal exposure during pregnancy, 33 6) pulmonary symptoms 29 and 7) accidents, particularly motor vehicle accidents. 34 Finally, frequent use of cannabis can cause significant withdrawal, which appears clinically similar to tobacco and opioid withdrawal, with symptoms of anxiety, irritability, depressed mood, disturbed sleep, decreased appetite and restlessness.…”
Section: Discussionmentioning
confidence: 99%
“…While some studies of in utero cannabis exposure have indicated low birth weight and stunted growth trajectories, others have found that these results depend upon the trimester during which the fetus was exposed [2,3,36,37] . In humans, low birth weight has been associated with an increased incidence of intraventricular hemorrhage, necrotizing enterocolitis, risk factors for infections, and respiratory distress, as well as neurodevelopmental and behavioral problems [38] .…”
Section: Discussionmentioning
confidence: 99%
“…As more states and countries throughout the world come to legalize medical and recreational use of marijuana, these figures are anticipated to rise. Cannabis use during pregnancy has been linked to low birth weight for age and smaller head circumferences in the offspring [2,3] . Although smaller head circumferences were noted, there was no difference noted in transcerebellar diameter in fetuses exposed to cannabis [3] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation